Applying systems thinking approaches to investigate the complex interrelationships of risk factors affecting acute non-contact lower limb injuries in team sports (PhD Academy Award) - Liveris, N. I. (British Journal of Sports Medicine, 2025)
The primary purpose of my PhD is to employ systems thinking and system dynamics methodologies to investigate the complex interrelationships among injury risk factors affecting acute non-contact lower-limb injuries, with a particular focus on hamstring injuries. First, I used qualitative Causal Loop Modelling (CLD) to evaluate the `bigger picture` of intrinsic and extrinsic risk factors` interrelationships that lead to hamstring injury. Second, I employed Partial Least Squares Structural Equation Modelling (PLS-SEM) to quantitatively assess the intrinsic risk factors` interrelationships and their effects on (1) hamstring injuriesand (2) the frequency of all acute non-contact lower limb injuries.